2016
DOI: 10.1007/s00266-016-0703-0
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Integra Dermal Regeneration Template Versus Flaps for Reconstruction of Full-Thickness Scalp Defects Involving the Calvaria: A Cost–Benefit Analysis

Abstract: BackgroundINTEGRA® Dermal Regeneration Template is a well-known and widely used acellular dermal matrix. Although it helps to solve many challenging problems in reconstructive surgery, the product cost may make it an expensive alternative compared to other reconstruction procedures. This retrospective study aims at comparing INTEGRA-based treatment to flap surgery in terms of cost and benefit.Patients and MethodsWe considered only patients treated for scalp defects with bone exposure in order to obtain two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 17 publications
0
68
0
2
Order By: Relevance
“…Dermal equivalents are used as off‐the‐shelf products in clinics such as MatriDerm®, Integra™, and DermaGraft®. These grafts combine autologous dermal fibroblasts and matrices based on various artificial, natural and synthetic materials, respectively . Combinations of epidermal and dermal grafts include PermaDerm™ and DenovoSkin, which are based on natural scaffold materials, fibroblasts and keratinocytes covering superficial wounds .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermal equivalents are used as off‐the‐shelf products in clinics such as MatriDerm®, Integra™, and DermaGraft®. These grafts combine autologous dermal fibroblasts and matrices based on various artificial, natural and synthetic materials, respectively . Combinations of epidermal and dermal grafts include PermaDerm™ and DenovoSkin, which are based on natural scaffold materials, fibroblasts and keratinocytes covering superficial wounds .…”
Section: Introductionmentioning
confidence: 99%
“…These grafts combine autologous dermal fibroblasts and matrices based on various artificial, natural and synthetic materials, respectively. [8][9][10][11][12] Combinations of epidermal and dermal grafts include PermaDerm™ and DenovoSkin, which are based on natural scaffold materials, fibroblasts and keratinocytes covering superficial wounds. 13 Issues that remain to be addressed include the risk of infection, poor adhesion and the temporary nature of the application.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its FDA approval for burns and diabetic foot ulcers, Integra has found increasing use all over the body for coverage of wounds that are not amenable to direct skin grafting. 6,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]…”
Section: Alternative Usesmentioning
confidence: 99%
“…The most widely studied role for Integra in the head and neck has been for coverage of full-thickness scalp wounds. [22][23][24] In a review of 34 studies, 32 showed success rates > 90%, with wounds described as large at 610 cm 2 . 23 Within these studies, the use of burring the outer table was frequently described to improve graft vascularization over denuded calvarium.…”
Section: Head and Neckmentioning
confidence: 99%
See 1 more Smart Citation